۹. ۵. ۷. ۲. الف) با کمک اتحاد مزدوج، حاصل‌ضرب عبارت‌ زیر را حساب کنید.
\[(x^3+2x^2-x+4)(x^3-2x^2-x-4)\]


راهنمای حل

\[\begin{aligned}&(x^3+2x^2-x+4)(x^3-2x^2-x-4)\\&=(x^3-x+2x^2+4)(x^3-x-2x^2-4)\\&=\big({\color{red}(x^3-x)}+{\color{blue}(2x^2+4)}\big)\big({\color{red}(x^3-x)}-{\color{blue}(2x^2+4)}\big)\\&={\color{red}(x^3-x)^2}-{\color{blue}(2x^2+4)^2}\\&={\color{red}(x^6-2x^4+x^2)}-{\color{blue}(4x^4+16x^2+16)}\\&=x^6-2x^4+x^2-4x^4-16x^2-16\\&=x^6-6x^4-15x^2-16.\end{aligned}\]

دیدگاه بگذارید

avatar
  Subscribe  
Notify of